The role of the Peace and Security Council and the Assembly of Head of States and Government of the African Union in pursuit of democratisation in Africa - Vahard, Patrice Ernest (University of Pretoria, 2008)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2007.